Persepsi Kepala Sekolah, Guru Dan Siswa Terhadap Sekolah Yang Menyenangkan Di SD Muhammadiyah Program Khusus Kotta Barat Surakarta - Ramadhani, Asri; , Murfiah Dewi Wulandari, S.Psi.,M.Psi Psikolog (2017)
This study aims to determine the principal, teacher, and student's perception of school fun. The type of this research is qualitative research with phenomenological approach. The data source of this research is principal, teachers, and students. Data collection techniques were used interviews, observation and documentation. Data validity of this research used triangulation. Data were analyzed interactively consisting of data collection, data reduction, data display, and conclusion and verification. The results showed that (1) The Principal understands exactly what was school fun; (2) Teachers are enjoying for educating and teaching at SD Muhammadiyah Surakarta Program Khusus Kotta Barat Surakarta; (3) The students feel happy when they are studying in SD Muhammadiyah Program Khusus Kotta Barat Surakarta